Statistical Mean Studying for Detected Intensities by Enet Web Camera for the White Test Image Under Different Fluorescent Lightness - Raouf, L. M.; Khathim, F. J.; Abass, H. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this work, is to study color filming by using different intensities of fluorescent light, where we evaluate the capture image qualities for the RGB bands and component of L. And we study the relation between the means of RGBL values of the images as a function of the power of fluorescent light circuit . From the results, we show that the mean Î¼ increases rapidly at low power values, then it will reach the stability at high power values.